“As crianças que são deixadas para trás”: uma análise de discursos sobre o ensino remoto ofertado aos alunos com deficiência na pandemia da covid-19 - Kneipp, Gabriella Marques (2024)
This work presents the research that was developed in the course of Master’s Degree in Education in the Graduate Program in Education at the Federal University of Santa Maria - UFSM, in the Research Line Special Education, Inclusion and Difference - LP3, and is linked to the Difference, Education and Culture Research Group DEC/CNPq. With the objective of analyzing speeches produced on remote schooling of students with disabilities during the COVID-19 pandemic, the study is methodologically affiliated to post-school theorizationscriticism in education, and provides for the production of analytical materiality from sets of documents: the first consists of legal norms produced during the pandemic period to normalize remote teaching; and the second one constituted of materials published on Internet sites during the pandemic period and also after this period, when students experienced the return to classroom schooling. The work of reading these materials made it possible to understand that, despite efforts and advances in inclusive policies, it is important to highlight some limitations for its implementation in schools, especially regarding lack of resources, socioeconomic inequalities, absence of the state, precarious training of teachers, lack of accessibility, among others. Such factors can impact the effectiveness of inclusive policies and practices and were emphasized in the pandemic context, bringing the weaknesses of inclusive practices during remote teaching. Among the set of complaints about these factors made by the analyzed subjects, it was possible to find speeches that indicate that remote schooling was mainly perverse with students, because it significantly limited their possibilities for physical interaction. According to such analysis, it is in the physical exchanges between students with and without disabilities that the greatest possibilities of transforming the school into a space effectively for all.